A Two-Step Hysteroscopic Management for Cesarean Scar Pregnancy: A Proposal Method - Giancarlo Garuti; Valeria Barbera; Monica Colonnelli; Beatrice Negri; Emanuela Bertazzoli; Marco Soligo (Clinical and Experimental Obstetrics & Gynecology, 2022)
Background: Cesarean Scar Pregnancy (CSP) is a cause of severe maternal morbidity. Currently, no guideline for its management is shared. We assessed safety and effectiveness of Methotrexate (MTX) administration within the sub-chorionic space under hysteroscopic guidance, followed by resectoscopic placental removal. Methods: Five patients suffering from type 2 CSP underwent a sequential treatment based on hysteroscopic techniques. Pregnancy termination was firstly obtained by injection of 80 mg of MTX within the intervillous spaces of placental site. The intervention was performed in an office setting using a 16Fr hysteroscope. MTX was administered by a 17-gauge needle suitable for the operative channel of hysteroscope. Subsequently, based on the decline of Human Chorionic Gonadotropin β-subunit (β-HCG), we timed a placental removal using a 27-Fr resectoscope, under conscious sedation. Results: In all women a diagnosis of CSP was achieved between 6 and 8 gestational age weeks. Hysteroscopic MTX administration resulted easily, quickly, painlessly and uneventfully in all patients. A substantial decrease of β-HCG was obtained in all patients within 15 days from the MTX administration. After a mean time of 27 days from MTX a resectoscopic removal of CSP was carried-out without any recorded adverse outcome. After 30 days from surgery β-HCG returned to non-pregnant level and normal physical findings were found in all patients. Conclusions: Hysteroscopy-guided MTX sub-chorionic administration resulted safe and effective for CSP termination. It was followed by successful and uneventful resectoscopic placenta removal in all patients. When hysteroscopy facilities are available, this combined therapy can be an option to treat CSP.